Hypoxia enhances the migration and invasion of human glioblastoma U87 cells through PI3K/Akt/mTOR/HIF-1α pathway. Issue 18 (12th December 2018) - Huang, Weiyi; Ding, Xiaopeng; Ye, Hanbing; Wang, Jingying; Shao, Junfei; Huang, Tao
Abstract : Widespread invasiveness, represented by the invasion and migration, is the most important characteristic of glioblastoma multiforme (GBM) and is the main reason for therapeutic failure and recurrence of the tumor. Hypoxia is one of the main microenvironment in determining tumor invasiveness. Therefore, intense efforts aimed at improved therapeutics are ongoing to demonstrate the molecular mechanisms governing GBM migration and invasion. This study aims to explore the role of phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/Akt/mTOR) pathway and its relationship with hypoxia inducible factor-1α (HIF-1α) in the migration and invasion of human glioblastoma U87 cells under hypoxia. In the study, we found that hypoxia could activate the PI3K/Akt/mTOR pathway associated with the enhancements of the migration and invasion of human glioblastoma U87 cells. When the PI3K/Akt/mTOR pathway and HIF-1α were inhibited by the siRNAs or inhibitors, the migration and invasion of human glioblastoma U87 cells were suppressed. Meanwhile, the expression of HIF-1α could be inhibited by the siRNA or inhibitors of PI3K/Akt/mTOR pathway. The aforementioned results demonstrate that hypoxia could induce enhancements of migration and invasion by activating PI3K/Akt/mTOR pathway by targeting HIF-1α in human glioblastoma U87 cells, which provide a theoretical basis for the treatments of GBM by targeting the PI3K/Akt/mTOR/HIF-1α pathway.